Evolution of Diffusion-Related Degradation of Polymeric Lubricant Under Laser Heating: A Molecular Dynamics Study - Li, Bei (2016)
Molecular dynamics simulation coupled with a modified coarse-grained bead-spring model is employed to investigate the diffusion-related degradation of lubricant film under laser heating. The lubricant surface morphology and depletion profiles during laser heating are studied. It is observed that lubricant film degrades due to thermal diffusion and undergoes severe depletion with increasing laser heating duration, resulting in raised ridges around the depleted zone. The diffusion width and depth are evaluated to further explore diffusion-related degradation instability. As expected, the diffusion depth increases rapidly with the heating duration and the laser power, while the width would fluctuate around a constant value after initial rapid rise and following slight reduction. In addition, a Gaussian temperature gradient is formed in the radial direction due to the thermal transfer between the heated and surrounding beads. It is also shown that the laser power plays an important role in the temperature gradient and hence greatly influences the diffusion-related degradation of lubricant film on a solid surface.